Seismicity-based 3D model of ruptured seismogenic faults in the North-South Seismic Belt, China - Rong, Yilin; Bai, Yongliang; Ren, Mengjiao; Liang, Mingjian; Wang, Zhenjie (Frontiers in Earth Science, 2023)
The North–South Seismic Belt produces the most frequent strong earthquakes in the Chinese continental region, and this seismicity causes significant hazards. A fault geometry model is crucial for analyzing earthquake preparation and trigger mechanisms, simulating and predicting strong earthquakes, inverting fault slip rates, etc. In this study, a novel method is designed based on datasets from surface fault traces, field geological surveys, geophysical prospecting and drilling, focal mechanism solutions, and earthquake relocations. The initial fault morphology is constructed from the focal mechanism solution data. This initial fault morphology is used to select the earthquake relocation data that are related to the target fault. Next, the fine fault morphology is fitted based on the selected earthquake relocation data. This method avoids the problem of constructing only a simplified low-resolution model based purely on focal mechanism solution data. Moreover, the interference of earthquake relocation data, which is related to adjacent faults, on fitting fault geometry is reduced under the constraints of initial morphology. Based on this method, the fine morphologies of different faults along 1,573 transverse profiles in the North–South Seismic Belt were fitted, and a three-dimensional model of 263 ruptured seismogenic faults (segments) in the North–South Seismic Belt was constructed using the minimum curvature spatial interpolation method. The model uncertainty increases with burial depth, and different fault models may have different uncertainties. The overall fitting error of the model is 0.98 km with respect to the interpreted results for six geophysical exploration profiles.